Three new records of the genus Carex (Cyperaceae) from Peru and additions to the Andean flora of the Huánuco department - De María Salvador, Flor (2008)
Three new records from Peru (Carex humahuacaensis G.A. Wheeler, Carex peucophila T. Holm y Carex pygmaea Boeck.), and 75 new records of vascular plants are reported for Huánuco department. Its habitat, distribution and the conservation status of endemisms such as: Caiophora cirsiifolia C. Presl, Carex hebetata Boott and Senecio macrorrhizus Wedd. are commented.